2017
DOI: 10.1002/sctm.16-0441
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Promotes the Stemness of Corneal Epithelial Stem/Progenitor Cells and Accelerates Epithelial Wound Healing in the Cornea

Abstract: High concentration of ascorbic acid (vitamin C) has been found in corneal epithelium of various species. However, the specific functions and mechanisms of ascorbic acid in the repair of corneal epithelium are not clear. In this study, it was found that ascorbic acid accelerates corneal epithelial wound healing in vivo in mouse. In addition, ascorbic acid enhanced the stemness of cultured mouse corneal epithelial stem/progenitor cells (TKE2) in vitro, as shown by elevated clone formation ability and increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…Moreover, Lameira et al showed that resveratrol can epigenetically alter 5‐hmC levels, and additional studies have linked resveratrol to stem cell proliferation and hair growth via the prostaglandin D2 pathway . Furthermore, ascorbic acid, a known promoter of epithelial stem cells, has also been shown to stimulate hair growth and alter 5‐hmC levels by modulating TET activity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Lameira et al showed that resveratrol can epigenetically alter 5‐hmC levels, and additional studies have linked resveratrol to stem cell proliferation and hair growth via the prostaglandin D2 pathway . Furthermore, ascorbic acid, a known promoter of epithelial stem cells, has also been shown to stimulate hair growth and alter 5‐hmC levels by modulating TET activity …”
Section: Discussionmentioning
confidence: 99%
“…5-hmC, 5-hydroxymethylcytosine; IHC, immunohistochemistry resveratrol can epigenetically alter 5-hmC levels, and additional studies have linked resveratrol to stem cell proliferation and hair growth via the prostaglandin D2 pathway [23][24][25]. Furthermore, ascorbic acid, a known promoter of epithelial stem cells, has also been shown to stimulate hair growth and alter 5-hmC levels by modulating TET activity 17,[26][27][28]. Using these agents known to modulate HF growth via epigenetic pathways, a subset of mouse BSCs in organ cultures underwent signs of activation, as indicated by Ki67 labeling.…”
mentioning
confidence: 99%
“…The mice corneal epithelial stem/progenitor cells used in this study have high expression levels of limbal progenitor cells markers ΔNp63 and importin 13 and have low expression levels of differentiated markers ck3/12 and involucrin, implying that these cells still retain stem cell properties. The TKE2 cells were cultured in keratinocyte serum‐free low‐Ca 2+ medium to maintain the undifferentiated state, and this cell line has already been characterized and used for the study of CESC and corneal wound healing in other reports . In addition, in order to validate our results from the TKE2 cells, we used primary cultured rabbit corneal epithelial cells for key experiments such as cell cycle and apoptosis detection.…”
Section: Discussionmentioning
confidence: 99%
“…that these cells still retain stem cell properties. The TKE2 cells were cultured in keratinocyte serum-free low-Ca 2+ medium to maintain the undifferentiated state, and this cell line has already been characterized and used for the study of CESC and corneal wound healing in other reports [40][41][42][43]. In addition, in order to validate our results from the TKE2 cells, we used primary cultured rabbit corneal epithelial cells for key experiments such as cell cycle and apoptosis detection.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate is considered to be important with respect to wound healing and prevention of corneal ulceration [5]. After an ocular burn, the disposability of ascorbate in the aqueous humor and the cornea may be reduced for weeks [6].…”
Section: Introductionmentioning
confidence: 99%